Colombia : Country Financial Accountability Assessment - World Bank (Washington, DC, 2012)
In recent years Colombia has made important progress in its PFM systems and improved transparency in public finance. Important initiatives include adoption of the 2002 presidential anticorruption plan, improving the administration of publicly owned banks, clarifying responsibilities for managing expenditures among different levels of government, and introducing modem accounting concepts and procedures. These initiatives were supported by the rollout of new information systems covering the budget and local government finances, as well as the monitoring of public procurement. The Government enacted an important Fiscal Transparency and Responsibility Law in 2003, and strengthened the disciplinary code for public servants. The Government also strengthened the laws regulating contingent liability management in 1998, and is building a systematic framework to track and manage contingent liabilities. Systems are being put in place to track counter-guarantees for sub-national governments, lawsuits, and arrears to providers, and two special funds have been established to manage specific contingencies. Despite this progress, there remain problems in managing other liabilities. Among them: The Government has run up significant arrears with providers, largely because anticipated budget allocations from Treasury have been curtailed by revenue shortfalls. In addition, the handling of pension liabilities and contingent liabilities related to lawsuits represents an important financial management weakness. These contingent liabilities are aggravated by the Government's weak capacity to defend itself in court, and a reluctance to pursue legal action against civil servants, which implies that corruption involves little risk. In addition, the legal framework needed to flesh out constitutional mandates is not yet fully in place and is sometimes unclear, particularly in the areas of budget and fiscal control.